Driving, Dropouts, and Drive-Throughs: Mobility Restrictions and Teen Human Capital - Valerie Bostwick; Christopher Severen (Institute of Labor Economics (IZA), 2023)
We provide evidence that graduated driver licensing (GDL) laws, originally intended to improve public safety, impact human capital accumulation. Many teens use automobiles to access both school and employment. Because school and work decisions are interrelated, the effects of automobile-specific mobility restrictions are ambiguous. Using a novel triple-difference research design, we find that restricting mobility significantly reduces high school dropout rates and teen employment. We develop a multiple discrete choice model that rationalizes unintended consequences and reveals that school and work are weak complements. Thus, improved educational outcomes reflect decreased access to leisure activities rather than reduced labor market access.
Keywords: I20; J24; J22; C35; R48; 330; mobility restrictions; human capital; teen employment; graduated driver licensing; multiple discreteness